Impacts of Cyclic Loading and Unloading Rates on Acoustic Emission Evolution and Felicity Effect of Instable Rock Mass - Mingwei Zhang; Qingbin Meng; Shengdong Liu; Deyu Qian; Nong Zhang (Advances in Materials Science and Engineering)
Uniaxial cyclic loading-unloading compression experiments with schemes of six loading rates and six unloading rates were carried out on the combined testing platform. Impact of loading and unloading rates on rock AE characteristics was revealed. Results show that increasing loading and unloading rates resulted in decreasing total AE rings in the entire rock deformation and failure process. Increasing loading rate decreased the AE rings at loading stages, and increasing unloading rate decreased the AE rings at unloading stages in the same cycle. Total AE counts had a negative linear relationship to the loading and unloading rates. The loading stage was the active period of the AE phenomena, and impacts of the loading rate on the AE characteristics were more apparent. Especially when the loading rate was greater than 2.0 kN/s, brittle failure of rock specimens became noticeable. After the cyclic load reached the uniaxial compressive strength of 1/3∼1/2 times, the rock Felicity effect became more obvious. With the increase of the loading rate, the Felicity ratio decreased in the elastic stage and increased a little in the plastic stage, whereas with the increase of the unloading rate, the Felicity ratio decreased gradually in the elastic stage and remained almost the same in the plastic stage.